Handbook of Self-Regulation. - Boekaerts, Monique (Elsevier, 1999)
The Handbook of Self-Regulation represents state-of-the-art coverage of the latest theory, research, and developments in applications of self-regulation research. Chapters are of interest to psychologists interested in the development and operation of self-regulation as well as applications to health, organizational, clinical, and educational psychology. This book pulls together theory, research, and applications in the self-regulation domain and provides broad coverage of conceptual, methodological, and treatment issues. In view of the burgeoning interest and massive research on various aspec.